2022
DOI: 10.3389/fpsyt.2021.774858
|View full text |Cite
|
Sign up to set email alerts
|

Child and Parent Physical Activity, Sleep, and Screen Time During COVID-19 and Associations With Mental Health: Implications for Future Psycho-Cardiological Disease?

Abstract: The COVID-19 pandemic has afforded the opportunity for some to improve lifestyle behaviours, while for others it has presented key challenges. Adverse changes in global lifestyle behaviours, including physical activity, sleep, and screen time can affect proximal mental health and in turn distal cardiovascular outcomes. We investigated differences in physical activity, sleep, and screen time in parents and children during early stages of the COVID-19 pandemic in Australia compared to pre-COVID-19 national data;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 62 publications
1
18
0
Order By: Relevance
“…The deleterious changes to health behaviors in US youth documented in this study are not unique to US youth, with similar changes in health behaviors during COVID documented among youth in Australia, Canada and China. 34,[36][37][38] Longitudinal research has shown that health behaviors during childhood are often carried over into adulthood, 39,40 suggesting if health behaviors do not return to pre-pandemic levels in youth, that could translate to potential increases in projected adverse physical (e.g., obesity, cardiovascular disease, diabetes) and mental health (e.g., depression, anxiety) outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The deleterious changes to health behaviors in US youth documented in this study are not unique to US youth, with similar changes in health behaviors during COVID documented among youth in Australia, Canada and China. 34,[36][37][38] Longitudinal research has shown that health behaviors during childhood are often carried over into adulthood, 39,40 suggesting if health behaviors do not return to pre-pandemic levels in youth, that could translate to potential increases in projected adverse physical (e.g., obesity, cardiovascular disease, diabetes) and mental health (e.g., depression, anxiety) outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Children and adolescents who spent 1-2 hours exercising showed a trend toward lower odds of psychological problems, and exercise for less than 30 minutes per day had a high probability of psychosocial problems. Psychosocial problems were linked to lower levels of physical activity [38][39][40]. Greater levels of physical activity are associated with improved physical fitness, bone health, cognitive outcomes, and mental health (reduced symptoms of depression) and less adiposity [36].…”
Section: Principal Findingsmentioning
confidence: 99%
“…They found even greater mental health issues for children who experienced a second lockdown. Olive et al ( 2022 ) found children experiencing COVID‐related declines in physical activity and increased recreational screen time were experiencing greater sleep disruption, elevated anxiety and irritability symptoms. The mental health of parents and carers, particularly those experiencing socioeconomic adversity, also declined (see Price et al, 2022 ).…”
Section: Covid ‐19 Responses and Opportunities To Access Ser...mentioning
confidence: 99%